A comparison of the effects of teaching through simulation and the traditional method on nursing students' self-efficacy skills and clinical performance: a quasi-experimental study - Marzieh Azizi; Ghobad Ramezani; Elham Karimi; Ali Asghar Hayat; Seyed Aliakbar Faghihi; Mohammad Hasan Keshavarzi (BMC, 2022)
Abstract Introduction Simulators in a clinical environment provide a space where students can acquire skills and experience under the supervision of their professors without any worries or inflicting any harm on their patients. The current study aimed to compare the effects of teaching through simulation and the traditional method on nursing students' self-efficacy skills and clinical performance. Method The current study was quasi-experimental and adopted a pre-test & post-test design. The population consisted of 122 students of nursing, out of whom 100 students were selected as the sample. Then, they were randomly divided into an experimental and a control group. A questionnaire assessed the students' self-efficacy skills and clinical performance before and after implementing the instructional programs. The data were analyzed using descriptive and inferential statistical techniques in SPSS 23. Findings The mean of the participants' self-efficacy scores increased significantly after the intervention (from 87.57 to 142.13). Moreover, the mean of the participants' clinical performance increased significantly after the intervention (from 2.16 to 4.57). The findings indicated that simulation teaching significantly affects nursing students' self-efficacy and clinical performance. Conclusion Simulation was recommended as an effective teaching methodology, particularly in nurses' internship wards. In other words, acquiring the essential skills through applying the simulation method is recommended before entering real-world environments.